Adaptions [sic] of fast mapping for vocabulary intervention with augmented language users. - Wilkinson KM; Albert A (AAC: Augmentative & Alternative Communication, 2001)
Over the past 20 years, a phenomenon called 'fast mapping' has received considerable attention as a potential explanation for the rapid vocabulary expansion typically observed in the preschool years. It has been proposed that children learn new words rapidly by sketching quick, incomplete maps of word meanings after only very few exposures to the word. Recently, several authors have suggested that adaptations of procedures used to explore fast mapping might be useful as an intervention tool for individuals with limited vocabulary associated with developmental delays. This article describes successful adaptation of fast mapping for teaching sight word recognition with two participants with cognitive and communication limitations. Important variations that were necessary to match teaching procedures to learning styles are highlighted across the two participants.